PSXIII-7 Effects of different organic pastures on dairy heifer rumen fluid characteristics. (8th October 2021) - Briggs, Reganne K; Hadfield, Jacob; Rose, Marcus; Stott, Rusty; Waldron, Blair; Young, Allen Y; Isom, Clay; Rood, Kerry; Thornton, Kara J
Abstract: This study investigates the effects that different forages in a rotational grazing system have on pH and VFA proportions of rumen fluid in organically raised dairy heifers. In 2018, 81 yearling Jersey heifers were assigned to one of nine treatments, including a conventional dry lot control (TMR) or one of eight pasture treatments. Pasture treatments included: tall fescue (TF), meadow bromegrass (MB), orchard grass (OG), perennial ryegrass (PR) and each individual grass interseeded with birdsfoot trefoil (BFT). Every 35-d, over a 105-d period, rumen fluid was collected using an oral stomach tube. Immediately following collection, pH was measured and recorded. Rumen fluid collected for VFA analysis was stabilized with acid and placed on wet ice and eventually frozen at -80° C until further analysis. Repeated measures analyses were performed using PROC MIXED in SAS (version 9.4) to determine how treatment affected each measurement over the total 105-day period. Time had a significant effect (P < 0.001) on pH ofrumen fluid over the 105-d growth period. Additionally, treatment had a significant effect (P < 0.001) on pH of rumen over the 105-d growth period. Animals that consumed the TMR diet had decreased rumen pH compared to other treatments. The proportions of acetate, propionate, isobutyrate, butyrate, isovalerate, and valerate were all significantly affected (P < 0.001) by time over the 105-d growth period. Treatment had an effect (P < 0.05) on the proportions ofpropionate and butyrate and had a tendency (P = 0.06) to affect the proportion of isovalerate. In general, animals on the TF pastures had decreased (P < 0.05) proportions of these VFAs in the rumen fluid. The proportions of acetate, isobutyrate, and valerate were not affected (P < 0.05) by treatment. These data provide insight into how different forages in organic pastures affect rumen characteristics of growing Jersey heifers.